2020
DOI: 10.1016/j.virusres.2020.198002
|View full text |Cite
|
Sign up to set email alerts
|

A highly pathogenic GI-19 lineage infectious bronchitis virus originated from multiple recombination events with broad tissue tropism

Abstract: In the present study, an IBV strain I0305/19 was isolated from a diseased commercial broiler flock in 2019 in China with high morbidity and mortality. The isolate I0305/19 was clustered together with viruses in sublineage D of GI-19 lineage on the basis of the complete S1 sequence analysis. Isolate I0305/19 and other GI-19 viruses isolated in China have the amino acid sequence MIA at positions 110-112 in the S protein. Further analysis based on the complete genomic sequence showed that the isolate emerged thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 75 publications
0
9
0
Order By: Relevance
“…Infectious bronchitis virus (IBV) is the prototype virus of Igacovirus subgenus, and various serotypes of IBV have been identified. IBV is the causal agent of infectious bronchitis that is prevalent worldwide and primarily infects the upper respiratory tract, but several IBV serotypes also infect kidney, digestive tract and reproductive system (Reddy et al 2015 ; Hou et al 2020 ). The genome of IBV contains at least 10 ORFs characterized by the following organization: 5’UTR-ORF1a/1b-S-3a-3b-E-M-5a-5b-N-3’UTR.…”
Section: The Taxonomy Host Range and Pathogenicity Of Cornidovirineaementioning
confidence: 99%
“…Infectious bronchitis virus (IBV) is the prototype virus of Igacovirus subgenus, and various serotypes of IBV have been identified. IBV is the causal agent of infectious bronchitis that is prevalent worldwide and primarily infects the upper respiratory tract, but several IBV serotypes also infect kidney, digestive tract and reproductive system (Reddy et al 2015 ; Hou et al 2020 ). The genome of IBV contains at least 10 ORFs characterized by the following organization: 5’UTR-ORF1a/1b-S-3a-3b-E-M-5a-5b-N-3’UTR.…”
Section: The Taxonomy Host Range and Pathogenicity Of Cornidovirineaementioning
confidence: 99%
“…The emerging IBV strain HH09 in this study was found to be generated through a recombination events between CK/CH/SCDY2003-2 and I0305/19. Of note, I0305/19 has been reported to be a highly pathogenic strain and has broader tissue tropism, including both the respiratory tissues and digestive tract tissues ( Hou et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the mutation and recombination of the S1 gene are crucial for the emergence of new IBV genotypes and serotypes. According to a classification scheme based on the S1 sequence, IBV strains have been classified into 36 lineages in 7 genotypes ( Valastro et al, 2016 ; Jiang et al, 2017 ; Ma et al, 2019 ; Hou et al, 2020 ; Molenaar et al, 2020 ). Due to this large number of serotypes and genotypes, IBV prevention remains to be a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…1 ). Because the JP-I genotype has been reported in China, Taiwan, and Japan ( 12 , 13 ), this information about the JP/KH/64 strain might be important for the understanding of IBV evolution in Eastern Asian countries.…”
Section: Announcementmentioning
confidence: 99%